In vitro and in vivo detection of microbial gene expression in bioactivated scaffolds seeded with cyanobacteria. (31st May 2022) - Leibrock, L.B.; Hofmann, D.M.; Fuchs, B.; Birt, A.; Reinholz, M.; Guertler, A.; Frank, K.; Giunta, R.E.; Egaña, J.T.; Nickelsen, J.; Schenck, T.L.; Moellhoff, N.
Abstract: Dermal replacement materials bioactivated with cyanobacteria have shown promising potential for wound regeneration. To date, extraction of cyanobacteria RNA from seeded scaffolds has not been described. The aim of this study was to develop a method to isolate total RNA from bioactivated scaffolds and to propose a new approach in determining living bacteria based on real‐time PCR. Transgenic Synechococcus sp. PCC 7002 (tSyn7002) were seeded in liquid cultures or scaffolds for dermal regeneration in vitro and in vivo for 7 days. RNA was extracted with a 260/280 ratio of ≥2. The small subunit of the 30S ribosome in prokaryotes ( 16S ) and RNAse P protein ( rnpA ) were validated as reference transcripts for PCR analysis. Gene expression patterns differed in vitro and in vivo . Expression of 16S was significantly upregulated in scaffolds in vitro, as compared to liquid cultures, whilst rnpA expression was comparable. In vivo, both 16S and rnpA showed reduced expression compared to in vitro ( 16S : in vivo Ct value 13.21 ± 0.32, in vitro 12.44 ± 0.42; rnpA in vivo Ct value 19.87 ± 0.41, in vitro 17.75 ± 1.41). Overall, the results demonstrate rnpA and 16S expression after 7 days of implantation in vitro and in vivo, proving the presence of living bacteria embedded in scaffolds using qPCR. Abstract : Significance and Impact of the Study: Bioactivated dermal replacement materials using cyanobacteria have shown promising results in enhancing wound healing. Most importantly, the survival of the micro‐organisms within the replacement material directly affects wound healing capacity. In this proof of principle study, we describe the development of a new approach that allows the detection of living cyanobacteria inside the scaffold in vitro and in vivo, based on real‐time PCR.